CATEGORICAL SPACES IN THE STATEMENTS AND SOLUTIONS OF THE PROBLEM OF CONSCIOUSNESS - Akopov , G.V. (Modern Psychology, 2019)
Substantial rethinking and expansion of terminological means for determining consciousness (qualia, subjectivity, access-consciousness, global workspace, etc.), as well as methodological foundations, approaches, and concepts allowed us to form a new field of interdisciplinary research in English-language sources (“Science of Consciousness»). The cultural and historical specificity of the development of scientific knowledge in various countries has led to certain differences in the terminological design of the problem of consciousness. Categories as fundamental concepts, together with interrelated concepts and terms, predetermine the formulation, approaches and conceptual solutions to the problem of consciousness. In this context, one can speak of various categorical “spaces» of the problem of consciousness. Categorical spaces of various theories of consciousness can be a tool not only for analyzing the integrity of a particular concept, but also for comparative as well as cross-cultural research.
Keywords: consciousness; category; problems of consciousness; different approaches; theories; sociocultural specificity; term; concept; categorical spaces